Best medical care practices in sport: investigating the barriers to the implementation in the developing countries. Uganda as a case study - Lubega, Samuelsaul (Department of Human Biology, 2021)
The dissertation consists of four separate studies that have focused on different aspects of the relationship between the management of sports related injuries and utilisation of best practices before sports, during sports and after sports-related injuries. Background: Participation in sports has an associated risk of injury which is defined by the type of sport and level of participation. Any injury affects the athletes‘ health status. To mitigate this risk, international sporting organizations provide guidelines, and mandates the proper evaluation and care for athletes before, during and after training or participation in competition. Despite the availability of guidelines describing best medical care practices for managing athletes, inappropriate management practices are reported globally. The barriers to best medical practice vary. While these barriers have been investigated in a variety of sports in developed countries, similar investigations have not been extensively conducted in developing countries, where the demands are different. Therefore, the overall aim of this thesis was to explore barriers to best medical practices in a variety of sports in Uganda. Methodology: The research was conducted as four studies. The first study used a descriptive case study approach. The data were collected on a sample of injured athletes (n=75) from four sports in Uganda (football/soccer, athletics, basketball and rugby) to describe the medical care practices of the sports resource providers. The current prevention, emergency care, intermediate treatment, rehabilitation services and return-to-sports strategies were all documented in a period of six months. The gaps in best practices were observed, and further investigated in the next three studies. Firstly, a validated questionnaire was used to establish the level of knowledge and practices of various components/themes of athletes‘ well-being and best practices among the stakeholders. Secondly, the current standards of the sports arenas and medical and high-performance facilities were examined using a validated checklist. The last study was a semi-structured interview which assessed the available national health care policies to support sports best practice strategies in Uganda Findings: The overall results of the first study showed there was a significant lack of compliance to best medical care practices in all the phases of athletes‘ health care. The barriers to best practice were confirmed as: (i) the lack of adequate knowledge and awareness on various best practice strategies, (ii) the sports and health facilities were below the required standards and, (iii) there were no national health sports care policies to support and facilitate the implementation of best practices in Uganda. Conclusion: (i) A holistic approach may be required to address the best medical care practice barriers in Uganda to improve on the health and safety of athletes. (ii) The knowledge of stakeholders should be improved and awareness created about best medical practices in sports in Uganda. (iii) There is a critical need to develop a national sports health care policy. (iv) The facilities for sports and health care of athletes urgently need improvement and supported.